Kemampuan Menulis Teks Biografi Menggunakan Teknik Tiru Model Berbantuan Media Video Pada Peserta Didik Kelas X SMA Negeri 1 Sipora Kabupaten Kepulauan Mentawai - Marzuki Saogo; Eva Fitrianti; Dwi Muthia Chan (JURNAL ARMADA PENDIDIKAN, 2023)
This study was motivated by three main issues: teachers had not used video media in instruction, students had not fully understood biographical texts due to inadequate sources and learning media, and students experienced difficulties in expressing their ideas in written form. The study aimed to describe Grade 10 students’ ability to write biographical texts at SMA Negeri 1 Sipora, Kepulauan Mentawai Regency, using video media through a model-imitation technique. The research employed a quantitative approach with a descriptive method. The population consisted of 96 Grade 10 students across four classes, and a sample of 48 students was selected using simple random sampling. The data were students’ performance-test scores on writing biographical texts. The results showed that: (1) the orientation indicator achieved a mean score of 99.30 (excellent/perfect qualification), (2) the significant events indicator achieved a mean score of 88.75 (very good qualification), and (3) the reorientation indicator achieved a mean score of 63.67 (fair qualification). Overall, students’ ability to write biographical texts using the model-imitation technique supported by video media obtained a mean score of 84.02, which falls into the good qualification. These findings indicate that video media effectively helps students understand the structure of biographical texts and supports writing performance, although the reorientation component still needs improvement.